DIAGRAM ALIR ALGORITMA KRUSKAL DALAM MENENTUKAN MINIMUM SPANNING TREE - Nina zakiah (JURNAL MATHEMATIC PAEDAGOGIC, 2021)
AbstractThe flow chart of the minimum spanning tree is represented in a weight matrix as a form of development of the link matrix. Determining the minimum spanning tree in this journal uses the Kruskal algorithm and is implemented in the form of a flow chart. This journal is a study of theories regarding the minimum spanning tree determination problem. With the problem approach, namely: graph theory, trees, determination of Minimum spanning tree, Kruskal's algorithm and flow diagrams. Furthermore, it is implemented in the flowchart of determining the Minimum spanning tree. Keywords: Minimum spanning tree, Kruskal's Algorithm, flow chart